1999
DOI: 10.1046/j.1365-2656.1999.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Viruses of the Serengeti: patterns of infection and mortality in African lions

Abstract: Summary1. We present data on the temporal dynamics of six viruses that infect lions (Panthera leo) in the Serengeti National Park and Ngorongoro Crater, Tanzania. These populations have been studied continuously for the past 30 years, and previous research has documented their seroprevalence for feline herpesvirus, feline immunode®ciency virus (FIV), feline calicivirus, feline parvovirus, feline coronavirus and canine distemper virus (CDV). A seventh virus, feline leukaemia virus (FeLV), was absent from these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
195
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(204 citation statements)
references
References 47 publications
6
195
2
1
Order By: Relevance
“…Lions in HiP were exposed to and became infected with various feline viruses, including FHV, FCV, FCoV, and FPV, with antibody prevalences comparable to those in other ecosystems (Packer et al, 1999;Spencer, 1992). We did not find any significant differences in prevalence of antibody to these viruses between inbred native and outbred translocated lions, suggesting that these diseases were not the reason for the decline of the inbred native HiP lion population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lions in HiP were exposed to and became infected with various feline viruses, including FHV, FCV, FCoV, and FPV, with antibody prevalences comparable to those in other ecosystems (Packer et al, 1999;Spencer, 1992). We did not find any significant differences in prevalence of antibody to these viruses between inbred native and outbred translocated lions, suggesting that these diseases were not the reason for the decline of the inbred native HiP lion population.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the bTB control program, the number of infected buffalos has been greatly reduced, which reduced the risk of spillover into predators. Therefore, one possibility for the absence of bTB deaths in the translocated animals and their offspring might be a long (Maddock et al, 1996;Trinkel et al, 2008), and inbred lions are especially susceptible to infectious disease (Packer et al, 1991;Kissui and Packer, 2004). Inbreeding depression, therefore, could explain the native HiP lions' high bTB infection rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Host density is of central importance to infection rates in directly transmitted parasites (Poulin, 1998), and intraspecific studies have demonstrated that host density positively correlates with parasite prevalence and diversity (Morand and Poulin, 1998;Packer et al, 1999). However, studies that have concurrently examined primate density and habitat characteristics in relation to primate parasite prevalence reveal that habitat characteristics may be a better predictor of parasitic infection than primate density is (Gillespie, 2004;Gillespie and Chapman, 2005;Stuart et al, 1993).…”
Section: Provide Supportive Datamentioning
confidence: 99%
“…Animal clusters and high contact rates with humans and/or domestic animals were linked to increase the prevalence of pathogens (Packer et al 1999). Certain infectious diseases, such as Salmonella, are commonly shared between humans, domestic animals and wildlife.…”
Section: Introductionmentioning
confidence: 99%